The Use of Exergames in the Neurorehabilitation of People with Parkinson Disease: The Impact on Daily Life - Zeigelboim,Bianca Simone (2021)
Abstract Introduction Parkinson disease (PD) is a progressive degeneration characterized by motor disorders, such as tremor, bradykinesia, stiffness and postural instability. Objective To evaluate the independence, confidence and balance in the development of daily activities in patients with PD before and after rehabilitation. Methods A descriptive, retrospective cross-sectional study was carried out with 16 patients (mean 57.6 ± 18.7 years), submitted to anamnesis, otolaryngological evaluation and vestibular assessment. The Vestibular Disorders Activities of Daily Living (VADL) and the Activities-Specific Balance Confidence (ABC) scales were applied before and after rehabilitation with virtual reality. Results a) The instrumental subscale of the questionnaire showed statistically significant result (p = 0.022; 95 % CI 1.21; 2.21) between the first and second assessments; b) The correlation between the questionnaires showed statistically significant result in the ambulation subscale (p = 0.011; 95 % CI -0.85; -0.17) first and (p = 0.002, 95 % CI -0.88; -0.31) second assessments, and the functional subscale was only verified in the second assessment (p = 0.011, 95 % CI -0.85; -0.17); and c) The patients presented clinical improvement in the final assessment after rehabilitation with significant result for the tightrope walk (p = 0.034, 95 % CI -12.5; -0.3) and ski slalom games (p = 0.005, 95 % CI -34.8; -6.6). Conclusions Our results showed that the VADL and ABC questionnaires, applied before and after rehabilitation, were important tools to measure the independence, confidence and balance while developing daily activities. The VADL and ABC questionnaires may effectively contribute to quantify the effect of the applied therapeutics and, consequently, its impact on the quality of life of patients with PD.